Trastuzumab Emtansine for the Treatment of HER-2 Positive Carcinoma Ex-pleomorphic Adenoma Metastatic to the Brain: A Case Report - Ihab Hassanieh; Ihab Hassanieh; Lara Hilal; Lara Hilal; Karine A. Al Feghali; Karine A. Al Feghali; Ibrahim Khalifeh; Bassem Youssef; Bassem Youssef (Frontiers in Oncology, 2018)
Background: Carcinoma Ex-pleomorphic adenoma is a malignant transformation of the common benign neoplasm of the salivary glands, “pleomorphic adenoma.” Only two cases were ever reported with brain metastases, with absence of good evidence guiding management of such cases.Case Presentation: A 61-year-old woman presenting with facial paralysis was found to have carcinoma ex-pleomorphic adenoma of the parotid gland. Twenty months after local treatment, she developed brain metastases, treated with whole brain radiation therapy. The patient then had progressive intracranial disease after the end of radiation therapy in addition to the appearance of liver metastases. Pathology showed overexpression of HER2, so she was treated with Trastuzumab Emtansine (TDM1). Follow-up imaging revealed significant decrease in the number and size of the metastatic brain lesions in keeping with a good response to TDM1 treatment.Conclusion: Prognosis of metastatic carcinoma ex-pleomorphic adenoma is very poor, and there is no clear management for such cases. We present a case of carcinoma ex-pleomorphic adenoma with brain and liver metastases with a very good response to TDM1 treatment.